SLANG WORDS OF MOVIE CLUELESS - Sari, Dewi Purnama; Syaputri, Komala Dwi; Hajiriah, Anggi (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2023)
Slang, as a linguistic phenomenon, serves as a means of informal communication within specific communities. This study delves into the analysis of slang usage in the film